Environmental Pollution, Terrorism, and Mortality Rate in China, India, Russia, and Turkiye - Bildirici, Melike E.; Genc, Sema Yilmaz; Castanho, Rui Alexandre (MDPI, 2022)
This paper tests the cointegration and causality between mortality rate, terrorism, economic growth, and environmental pollution in China, India, Russia, and Turkiye in the period from 1990 to 2021 by using the Fourier bootstrapping auto-regressive distributed lag (FBARDL) test and Granger causality with Fourier (FGC) test. The FBARDL test determined cointegration between the selected variables. The FGC test found the evidence of causality among the selected variables. For Russia, Turkiye, India, and China, we found evidence of unidirectional causality running from terrorism to environmental pollution. The evidence of one-way causality from economic growth to environmental pollution was determined for Turkiye and China, but, for India and Russia, we found one-way causality from environmental pollution to economic growth. We found unidirectional causality from terrorism to mortality rate for Turkiye and China. For Russia, we found evidence of none causality. In addition, we determined there was evidence of unidirectional causality from environmental pollution to morality rate.
Keywords: Fourier bootstrapping auto-regressive distributed lag (FBARDL); Granger causality with Fourier; mortality rate; terrorism; economic growth; environmental pollution; FOREIGN DIRECT-INVESTMENT; ECONOMIC-GROWTH; CO2 EMISSIONS; TRANSNATIONAL TERRORISM; COINTEGRATION; PERIOD; Science & Technology - Other Topics; Environmental Sciences & Ecology